DEMAND FOR MONEY AND LONG RUN STABILITY IN GHANA: COINTEGRATION APPROACH - K. Havi, Emmanuel Dodzi; Enu, Patrick; Opoku, C.D.K (European Scientific Journal, ESJ, 2014)
This paper examined the demand for broad money and its long run stability in Ghana. Multivariate time series approach was used. Since all the variables are integrated of order one, Johansen’s cointegration approach is used to establish that the variables are cointegrated. Hence, vector error correction model was used to find the determinants of broad money. Also, CUMSUM and CUMSUMSQ plots are used to check the long run stability of the demand function. It was established that nominal foreign interest rate and expected inflation were long run determinants of demand for money while real income and nominal exchange rate were short run determinants. Also, it was found that the long run broad money demand function was stable over the period under consideration. It was recommended that monetary policy authorities should continue to implement policies that will enhance macroeconomic stability (price stability) and facilitate economic growth.